Factors Associated with Pre-Research Recruitment in Autism and Related Developmental Disorders. - Karnik, Ashwin; Malhi, Gurjot; Ho, Theodore; Riffle, Stacy; Keller, Kylie; Kim, Soo-Jeong (Journal of Autism & Developmental Disorders, 2025)
Purpose: Access to research programs and increased diversity in research enrollment may be key to improving diverse populations' health and healthcare outcomes. To facilitate research recruitment, a Research Registry ("Registry"), a pre-recruitment database, was developed at an urban tertiary Autism Center ("Autism Center"). In this study, we examined whether disparities in research participation occur in the pre-research recruitment (pre-recruitment) stage. Methods: We compared demographic factors of patients seen at the Autism Center (but not enrolled in the Registry) vs. patients enrolled in the Registry. We also examined whether demographic factors differ among the Registry participants who were enrolled in the Registry by signing an informed consent form (ICF) vs. by returning a research interest form (RIF). Results: A total of 18,522 patients (including 1092 patients in the Registry with 403 patients via ICF and 689 patients via RIF) were included in this study. English as the primary language, White race, Non-Hispanic ethnicity, and younger age at their first clinic encounter were associated with the Registry. In the Registry sample, the RIF group had a higher proportion of non-English as a primary language, Medicaid insurance, longer distance from the Autism Center, and lower median household income (based on their ZIP code) than the ICF group. Conclusions: This study suggests that disparities may have existed in the pre-research recruitment stage. To achieve equity in both clinical and research advancements in autism and related developmental disorders, further efforts are needed to equitably disseminate research opportunities to patients of diverse backgrounds.